The potential of LiDAR application in Malaysia. - Ismail, Mohd Hasmadi; Manaf, Mohamad Sam (2011)
Remote sensing technology has grown over time and will continue in the future. Malaysia is aware of the emerging of remote sensing technology including LiDAR system in the market. The technology can offers an advantages and benefits in managing natural resources. Dealing with advance sensing technologies and analytical tools to support site-specific economic, environmental, and sustainable decision making, the accurate, timely and detailed spatial information or features characterization are requires. Despite of the current use of high resolution satellite and airborne sensing, LiDAR is a promising alternative tool to be used in especially in forestry sector. This is possible by utilization of accurate measurement forestry data and information to improve operations and processes. As a newcomer in LiDAR technology this paper gives a synopsis of LiDAR sensing technology application and its potential to Malaysia.